Pemanfaatan Aplikasi Canva sebagai Media Pembelajaran Menulis Teks Iklan bagi Siswa SMP - Rotunnaja, Nina Ina; Ambia, Tintina Putri; Taufik, Indra Nugrahayu (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Writing skills are one of the language skills that are often considered difficult. This is reflected in the lack of interest among students in writing activities. One of the writing activities that is quite challenging is writing advertisement texts, because conveying thoughts or information involves not just writing but also requires various attractive images and colors. Therefore, it is necessary to use learning media that can support educators in delivering the material for writing advertisement texts. In this digital era, educators should indeed take advantage of technology and digitalization in the learning process. One alternative that can support the activity of writing advertisement texts is the use of the Canva application for writing and designing ads or posters. This is because Canva is one of the applications that provides tools for creating infographic designs, posters, videos, graphics, brochures, logos, presentations, and more. So this research aims to determine the utilization of the Canva application in writing advertisement texts. The method used in this research is qualitative descriptive analysis. The results of this study indicate that the Canva application can support the ability to write advertising texts for middle school students. This is because the application provides a variety of features that can aid in learning to write advertising texts.